Photoaging Reversibility in Asian Patients With Melasma Treated Using Picosecond Lasers With a Diffractive Lens Array: A 1-Year Prospective Observational Cohort Study. Issue 1 (January 2021) - Lin, Erh-Ti; Chiang, Hsiu-Mei; Lin, Bor-Shyh; Huang, Yung-Hsueh; Chang, Chang-Cheng
Abstract : BACKGROUND: Picosecond lasers appear to be effective and safe in treating pigmentation and photoaging disorders through laser-induced optical breakdown. OBJECTIVE: To analyze the feasibility of photorejuvenation using picosecond lasers with diffractive lens array (DLA) in patients with melasma. METHODS: Ten Asian ( N = 10) women with melasma and Fitzpatrick skin Type IV were enrolled and treated using 755-nm picosecond alexandrite lasers with DLA. All individuals were assessed before treatment, and at 12, 20 weeks, and 1 year by post-hoc test on melasma area and severity index (MASI) and with VISIA Complexion Analysis System using percentile rank for measurement. RESULTS: The median participant age was 46.5 years. The average MASI continually and significantly ( p < .05) decreased until the 1-year follow-up, with the photoaging characteristics, such as wrinkles and red areas improving simultaneously ( p < .05). Spots, texture, pores, ultraviolet (UV) spots, brown spots, and porphyrins exhibited alleviation, but this improvement relapsed by the 1-year follow-up. No postinflammatory hyperpigmentation or hypopigmentation occurred. CONCLUSION: In patients with melasma, picosecond laser treatment with DLA may alleviate pigmentation disorder and the related photoaging characteristics (e.g., wrinkled skin and increased vascularity), and the effects may be maintained for a long time. Nevertheless, post-treatment clinical visits every 3 to 6 months are recommended. Abstract : Supplemental Digital Content is Available in the Text.